258 ACCURACY OF PATIENT-INITIATED VERSUS ROUTINE TRANSMISSIONS OF VENTRICULAR ARRHYTHMIA DATA OVER A HOME DEFIBRILLATOR LINK SYSTEM. (1st January 2006) - Bissett, J. K.; Clark, J.; Mabry, V.
Abstract : Purpose: The purpose of this study was to compare the yield of positive versus negative transmissions for arrhythmia detection over the care link remote defibrillator (ICD) interrogation system using both routine scheduled ICD interrogation and patient-initiated transmissions. Methods: Remote care link transmissions were evaluated in 70 male patients divided into routine scheduled data transmissions (RST) and event-driven remote transmissions based on the patient's perception of an arrhythmia (EDT). A maximum of one tracing per group per patient was used. The incidence of positive tracings for life-threatening arrhythmias including ventricular tachycardia and ventricular fibrillation (VT/VF) is shown below with cycle lengths for 10 transmissions. All patients had spontaneous arrhythmia termination or successful cardioversion or defibrillation by the ICD. Patients age 70 or greater had significantly fewer positive transmissions for VT/VF 2/32 (6.25%) versus positive transmissions for VT/VF in patients less than 70 years old 11/38 28.95%, p = .028, odds ratio 4.63 (1.107-19.38). Conclusions: (1) Although relatively few patients used the care link system for event-driven or patient-initiated transmissions, the initial yield for documentation of ventricular arrhythmias was encouraging. (2) The care link system has the potential to allow rapid diagnosis of changes in clinical status through the use of event-driven transmissions. (3) Additional study is required to verify and determine the effect of age on VT/VF in this population and the influence of clinical factors and patient selection.